2021
DOI: 10.1038/s41385-021-00390-x
|View full text |Cite
|
Sign up to set email alerts
|

The aryl hydrocarbon receptor regulates expression of mucosal trafficking receptor GPR15

Abstract: GPR15 is a chemoattractant receptor that facilitates colon homing of regulatory and effector CD4 + T cells in health and colitis. The molecular mechanisms that control GPR15 expression are not fully known. Here we report the presence of two highly conserved aryl hydrocarbon receptor (AHR) binding sequences in a 3′ enhancer of GPR15, leading us to investigate AHR function in regulating GPR15 expression. Using luciferase reporter assays, we show that AHR activation increased GPR15 expression and requires both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“… 27 It has been shown that regulatory T cell GPR15 expression in UC patients is increased 28 and, most recently, the dependence of GPR15 transcription on aryl hydrocarbon receptor signalling has been demonstrated. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 27 It has been shown that regulatory T cell GPR15 expression in UC patients is increased 28 and, most recently, the dependence of GPR15 transcription on aryl hydrocarbon receptor signalling has been demonstrated. 29 …”
Section: Discussionmentioning
confidence: 99%
“…In a T cell transfer model of colitis, the suppressive effect of Tregs on intestinal inflammation was diminished by the specific depletion of Ahr in Tregs ( 66 ). Whole-body Ahr deficiency acutely attenuates the expression of GPR15 both in effector memory T cells and in Tregs ( 67 ). Like SCFAs, AhR upregulates GPR15 expression together with FOXP3 in Tregs.…”
Section: Microbial Regulation Of Intestinal Tregsmentioning
confidence: 99%
“…Therefore, it remains unclear whether 3-MC promotes GATA3-dependent AhR binding in T-47D cells genome-wide, or only in a subset of AhR-enriched regions. Additionally, synergistic effects of GATA3 and AhR binding on the expression of GPR15 have been reported in human CD4+ T cells (Swaminathan et al, 2021), suggesting that AhR-GATA3 interactions might not be confined to breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%